2016
DOI: 10.5812/ircmj.21694
|View full text |Cite
|
Sign up to set email alerts
|

The Most Common Herbs to Cure the Most Common Oral Disease: Stomatitis Recurrent Aphthous Ulcer (RAU)

Abstract: Context:Recurrent aphthous ulcer (RAU) is an oral disease and the most common oral lesion, with 2% to 66% of the world’s population infected annually. Its prevalence is about 25% in Tehran and 27.6% in Mashhad. The etiology of RAU is multifactorial. Aphthous risk factors include: immunological factors, psychological factors, stress, trauma, sensitivity, family history, blood disorders, malnutrition, and use of certain medications, It should be noted that the best treatment for RAU is the topical application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…coriaria are used to treat diarrhea, while in Russia and Central Asia for dermatological problems . Furthermore, different parts of this plant are used as ingredient into gastrointestinal and ophthalmological remedies . Leaves of this genus are used as pigments due to its abundant content of chlorophyll, carotenoids, and tannins .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coriaria are used to treat diarrhea, while in Russia and Central Asia for dermatological problems . Furthermore, different parts of this plant are used as ingredient into gastrointestinal and ophthalmological remedies . Leaves of this genus are used as pigments due to its abundant content of chlorophyll, carotenoids, and tannins .…”
Section: Introductionmentioning
confidence: 99%
“…[6] Furthermore, different parts of this plant are used as ingredient into gastrointestinal and ophthalmological remedies. [7] [8] Leaves of this genus are used as pigments due to its abundant content of chlorophyll, carotenoids, and tannins. [9] [10] Previous studies in the literature showed the anticancer, antimicrobial, antioxidant, antidiabetic, anti-hypertensive and hypercholesteremic properties as well as the DNA-protective effect of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the treatment principle aims to reduce the inflammation, pain, and ulcer duration and prevent recurrence [4]. The present drug therapy includes mainly glucocorticoid, analgesic, immunomodulator, and Chinese medicine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this study is to explore the views, use of and access to TM among different ethnicities living in New Zealand, the impact of TM may have on dental care could be explored in future studies. (18) Massage therapy (22) Acupuncture 23Headache Chinese essential oil Chinese herbal concoction (24) Hijama (25) Head banding (25) Neck pain Chinese herbal patch Chinese herbal patches (26) Acupuncture (27) Acupressure (27) Cupping (27) Declining use of TM in New Zealand…”
Section: Use Of Tm In Different Conditionsmentioning
confidence: 99%